Analysis of potential genes and pathways associated with the colorectal normal mucosa–adenoma–carcinoma sequence. (16th April 2018) - Wu, Zhuoxuan; Liu, Zhen; Ge, Weiting; Shou, Jiawei; You, Liangkun; Pan, Hongming; Han, Weidong
Abstract: This study aimed to identify differentially expressed genes (DEGs) related to the colorectal normal mucosa–adenoma–carcinoma sequence using bioinformatics analysis. Raw data files were downloaded from Gene Expression Omnibus (GEO) and underwent quality assessment and preprocessing. DEGs were analyzed by the limma package in R software (R version 3.3.2). Gene Ontology (GO) enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were performed with the DAVID online tool. In a comparison of colorectal adenoma ( n = 20) and colorectal cancer (CRC) stage I ( n = 31), II ( n = 38), III ( n = 45), and IV ( n = 62) with normal colorectal mucosa ( n = 19), we identified 336 common DEGs. Among them, seven DEGs were associated with patient prognosis. Five ( HEPACAM2, ITLN1, LGALS2, MUC12, and NXPE1 ) of the seven genes presented a sequentially descending trend in expression with tumor progression. In contrast, TIMP1 showed a sequentially ascending trend. GCG was constantly downregulated compared with the gene expression level in normal mucosa. The significantly enriched GO terms included extracellular region, extracellular space, protein binding, and carbohydrate binding. The KEGG categories included HIF‐1 signaling pathway, insulin secretion, and glucagon signaling pathway. We discovered seven DEGs in the normal colorectal mucosa–adenoma–carcinoma sequence that was associated with CRC patient prognosis. Monitoring changes in these gene expression levels may be a strategy to assess disease progression, evaluate treatment efficacy, and predict prognosis. Abstract : We discovered seven DEGs through normal colorectal mucosa–adenoma–carcinoma associated with CRC patient prognosis. Monitoring changes in these gene expression levels makes it possible to assess disease progression, evaluate treatment efficacy, and predict prognosis. And our study provides a set of useful targets for further functional research, exploring the molecular mechanisms and uncovering new therapeutic targets.